2019
DOI: 10.1089/aid.2019.0058
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Characterization of Human Immunodeficiency Virus Type 1 Isolated from Antiretroviral Treatment-Experienced Individuals in Buleleng Regency, Bali, Indonesia

Abstract: Genotypic characterization of human immunodeficiency virus type 1 isolated from ARTexperienced individuals in Buleleng Regency,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Subtyping results were consistent with previous studies. [4][5][6][7][8][9] The CRF01_AE was found to be a predominant CRF among HIV-infected treatmentnaive individuals in Jakarta. The CRF is known to predominantly circulate in Southeast-Asian countries, including Thailand and Malaysia, 18,19 as well as in East-Asian countries, including Taiwan, China, South Korea, and Japan.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Subtyping results were consistent with previous studies. [4][5][6][7][8][9] The CRF01_AE was found to be a predominant CRF among HIV-infected treatmentnaive individuals in Jakarta. The CRF is known to predominantly circulate in Southeast-Asian countries, including Thailand and Malaysia, 18,19 as well as in East-Asian countries, including Taiwan, China, South Korea, and Japan.…”
Section: Discussionmentioning
confidence: 93%
“…These results suggest that CRF01_AE was the predominant CRF in Jakarta, similar to other regions in Indonesia. [4][5][6][7][8][9]…”
Section: Hiv-1 Subtypingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent study reported high prevalence of HIV transmitted drug resistance and moderate prevalence of acquired drug resistance among PLHIV residing in Buleleng, Bali, Indonesia. Drug resistance reduces the effectiveness of ART in suppressing HIV replication [22], [23]. This issue should be taken into consideration to delivered appropriate treatment in both ART-naive and ART-experienced individuals, especially when HHV-8 infection present.…”
Section: Discussionmentioning
confidence: 99%